2022
DOI: 10.3310/vlfl1739
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive testing for early detection of neovascular macular degeneration in unaffected second eyes of older adults: EDNA diagnostic accuracy study

Abstract: Background Neovascular age-related macular degeneration is a leading cause of sight loss, and early detection and treatment is important. For patients with neovascular age-related macular degeneration in one eye, it is usual practice to monitor the unaffected eye. The test used to diagnose neovascular age-related macular degeneration, fundus fluorescein angiography, is an invasive test. Non-invasive tests are available, but their diagnostic accuracy is unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 112 publications
0
4
0
Order By: Relevance
“…Earlier studies showed slow choroidal filling in AMD eyes through dye tests, not necessarily colocalized with drusen, indicating that a continuous layer of debris in BrM may reduce the metabolic exchange between the RPE and the choroid [ 62 , 63 ]. The invasive dye tests were progressively replaced by non-invasive technologies providing an increasingly better definition of choroidal anatomical planes and structures [ 64 ]. Currently, commercially available instrumentations enable qualitative and quantitative assessments of choroidal vessels and the CC.…”
Section: Choroidal Imaging and Assessment In Vivomentioning
confidence: 99%
“…Earlier studies showed slow choroidal filling in AMD eyes through dye tests, not necessarily colocalized with drusen, indicating that a continuous layer of debris in BrM may reduce the metabolic exchange between the RPE and the choroid [ 62 , 63 ]. The invasive dye tests were progressively replaced by non-invasive technologies providing an increasingly better definition of choroidal anatomical planes and structures [ 64 ]. Currently, commercially available instrumentations enable qualitative and quantitative assessments of choroidal vessels and the CC.…”
Section: Choroidal Imaging and Assessment In Vivomentioning
confidence: 99%
“…Both trials were limited by reliance on self-reported AMD status, confirmed by medical reports. Self-reporting is known to be inaccurate, especially for early stages of AMD …”
Section: Discussionmentioning
confidence: 99%
“…Self-reporting is known to be inaccurate, especially for early stages of AMD. [44][45][46][47][48][49] Suggestions of a benefit from aspirin therapy were also supported by the California Men's Health Study 15 and the California Teachers Study. 16 Both studies relied on selfreported aspirin use and AMD status identified from hospital discharge records.…”
Section: Discussionmentioning
confidence: 99%
“…OCT measures the light reflection of different tissues and analyzes it with software to form a tomographic image of the internal structure of the tissue [18]. As a non-invasive examination, OCT has been widely used in the diagnosis and treatment of various ophthalmic diseases and has gradually become an indispensable part of the ophthalmic examination [19,20]. OCT technology has advanced from time-domain (TD) to spectral-domain (SD), and swept-source (SS) OCT.…”
Section: Optical Coherence Tomography In Pcvmentioning
confidence: 99%